A Transform-Domain Robust Watermarking Model Using Discrete Wavelet Transform for Image Copyright Security - Randi Rizal; Nazwa Auliarahman; Siti Rahayu Selamat; Mae B. Lodana (JICO: International Journal of Informatics and Computing, 2025)
This research presents the development of a Discrete Wavelet Transform (DWT)–based method designed to strengthen digital copyright protection in images. The proposed approach leverages multi-resolution decomposition to embed copyright information within high-frequency and mid-frequency sub-bands, enabling improved resistance against common image attacks such as compression, noise addition, and geometric manipulation. Experimental evaluation shows that the method maintains high imperceptibility, with minimal impact on visual quality, while achieving strong extraction accuracy under various distortion scenarios. The results confirm that DWT remains a reliable foundation for constructing secure and robust watermarking mechanisms suitable for modern digital content protection needs.